USING PICTURE OF LUWU CULTURE ACTIVITY FOR TEACHING VOCABULARY - Langi, Nurdiana Tandi; Masruddin; Ermawati; Husnaini (FKIP Unismuh Makassar, 2024)
The purpose of this study was to determine whether or not junior high school students in Palopo, Indonesia, could effectively increase their vocabulary through the usage of pictures of Luwu culture activity. It applied pre-experimental research with one group pre-test and post-test design. The 210 eighth grade students at a junior high school in Palopo during the 2024 academic year represented as the research population. Class 8, which was an experimental class with 33 students, served as the sample. To gather data, the researcher employed tests. A quantitative analysis was conducted on the data. The results showed that students' vocabulary can be improved by integrating pictures of Luwu culture in their activities. The value of the t-test verified it. The t-test value of 11.853 was greater than the t-table value of 2.021. This number indicates that there was significant difference between the students’ pre- and post-test results. It was determined that using pictures of Luwu culture activities can help students become more proficient with vocabulary.